Nuclear energy consumption and economic growth : evidence from states level in the United States - Tan, Chiang Ching (Universiti Malaysia Sarawak, 2011)
This study attempts to investigate the casual relationship between nuclear energy consumption and economics growth in 10 selected states of the US from the period of 1970 to 2008. test for unit roots, cointegation, Granger causality and Variance Decomposition are presented.